Single-molecule probing of incommensurate biphenyl - Pärs*, M.; Palm, V.; Kikas, J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Our data on the distribution of purely-electronic linewidths of terrylene single molecules in incommensurate biphenyl crystals are compared with the data of other groups for different low-temperature organic solid hosts and with results of numerical simulations. The first two moments of the distributions measured within a narrowtemperature interval have been used to calculate a single dimensionless parameter characterizing each of therespective hosts — the variation coefficient. It appears that different amorphous hosts have similar values of this coefficient, but the value obtained for the incommensurate crystal of biphenyl is significantly different. One can conclude that the remarkable single-molecule line broadening in biphenyl at 1.8 K cannot be solely explained by the interaction with two-level systems, which is considered to cause the broadening in amorphous hosts.